PELANGGARAN PRIVASI DI AKUN INSTAGRAM LAMBE TURAH YANG DIAKIBATKAN OLEH VOYEURISM (PENDEKATAN PSIKOANALIS) - Yunus Winusa; Muhammad Rayhan Bustam (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2021)
Humans who are born in this era as social beings have a way of connecting with others, through continuous communication. To meet these needs, humans begin the development of technology and innovation which is closely related to information technology, especially on social media. Social media such as Instagram appears in the community the same as others, namely there are positive and negative sides behind it. The positive element is how easy it is to share information and make information available to the public, and the negative element is how the information is made available through violations caused by mediated voyeurism. The theories used in this study are voyeurism, surveillance, and psychoanalysis. The method used in this study is indirect qualitative observation to determine the existence of objects, situations, contexts, and meanings in an effort to collect research data. Voyeurism is generally known as deviant sexual behavior now covers a wide area. In today's digital world, the act of mediated voyeurism is getting wider, especially with a psychoanalysis approach. By performing mediated voyeurism behavior, users can get information about the daily privacy activities of other users, such as the Lambe Turah account on Instagram. Based on this incident, this study uses Instagram as an example of social media activity, because Instagram is one of the social media.